Semianalytic Finite-Element Method in Dynamic Problems of Linear Fracture Mechanics - Bazhenov, V. A.; Vabishchevich, M. O.; Solodei, I. I.; Chepurnaya, E. A. (International applied mechanics, 2018)
An effective approach to the simulation of crack-type fracture is developed based on the semi-analytical finite element method. Algorithms for determining the parameters of fracture strength for elastic bodies of revolution and prismatic bodies under non-stationary force loading of different intensity and duration are proposed. The energy approach based on the application of a special prismatic and ring finite elements with crack under dynamic loading are used to calculate the fracture parameters. The efficiency of the algorithms is estimated.